2020
DOI: 10.1007/s00127-020-01874-0
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversity and common mental disorders in young employees in Sweden: is the association affected by early adulthood occupational class?

Abstract: Background Childhood adversities are associated with an elevated risk for common mental disorders (CMDs). Whether the strength of the association also holds for young employees is unclear. Given the increase in CMD rates in young adults over the past decade, identification of risk factors has important implications for future public health interventions. The current study aimed to investigate the effects of childhood adversities on CMDs. Additionally, the role of occupational class (non-manual/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Our findings concerning the trigger explanation confirm and complement epidemiological knowledge of the associations of childhood adversity and mental disorders (Björkenstam et al., 2021) and related disability pension (Merikukka et al., 2018) in young adulthood. The trigger explanation demonstrates that although mental health problems may be rooted in the distant past, environmental factors such as working conditions could affect whether these symptoms resurface or not.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings concerning the trigger explanation confirm and complement epidemiological knowledge of the associations of childhood adversity and mental disorders (Björkenstam et al., 2021) and related disability pension (Merikukka et al., 2018) in young adulthood. The trigger explanation demonstrates that although mental health problems may be rooted in the distant past, environmental factors such as working conditions could affect whether these symptoms resurface or not.…”
Section: Discussionsupporting
confidence: 88%
“…Cumulative childhood adversity is also linked to mental health problems in later life periods. Such mental health problems might include anxiety, depression, eating disorders, self-harm behaviors, internalizing problems, externalizing problems, antisocial behavior, and personality disorder, among others ( Turner and Butler, 2003 ; Schilling et al, 2008 ; Putnam et al, 2013 ; McLaughlin, 2016 ; Björkenstam et al, 2017 , 2021 ; Steine et al, 2017 ; Hébert et al, 2018 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…22 CAs have been associated with occupational class, such that the prevalence of CAs is higher in manual workers. 23 Moreover, epidemiological studies on socioeconomic inequalities in LMM have consistently shown that manual workers have an elevated risk for unemployment, 24 SA 25 and DP. 26 Still, studies examining whether there are differences between manual and non-manual workers in the CA and LMM relationship in young employees are lacking to date.…”
Section: Introductionmentioning
confidence: 99%